Corrosion inhibitors for steel in concrete : state of the art report - Elsener, Bernhard (Publications (European Federation of Corrosion) ;, 2001)
This report describes in detail the different commercial inhibitors available for use in concrete and considers their mechanistic action together with experience from laboratory and field tests. Also deals with the possible effects of inhibitors on concrete properties and with their long term efficiency. Various test methods for evaluating the behaviour of corrosion inhibitors for steel in concrete are described and critically assessed.